Feasibility, safety, and efficacy of subcutaneous peripheral nerve field stimulation for the treatment of refractory low back pain: a two-year single-center Study - Ishak, Basem; Campos, Benito; Brunn, Heike; Unterberg, Andreas; Ahmadi, Rezvan (Neuroscience, 2018)
Chronic low back pain (CLBP) is challenging to treat. Minimal invasive neurostimulation therapies, such as subcutaneous peripheral nerve field stimulation (SPNS), improve pain relief and quality of life. The goal of the present study was to assess the usefulness, safety, and efficacy of SPNS in patients with CLBP. Twenty-six consecutive patients with CLBP were prospectively included in the study. For trial neurostimulation, two electrodes were implanted vertically at a depth of 1cm into the subcutaneous tissue, ≤10cm from the region of maximum pain. Trial neurostimulation was performed in all patients for 14days. A successful outcome was defined as at least 50% pain relief. To monitor the effects of permanent neurostimulation, the Visual Analog Scale (VAS), the Oswestry Disability Index (ODI), and quality of life (EQ-5D-3L) were scored preoperatively and at 6-month and 24-month follow-ups. Thirteen patients responded to trial stimulation and had a permanent neurostimulator implanted. The use of pain medication, including opioid analgesics, was reduced in 92% of patients after 24months. VAS, ODI, and EQ-5D-3L scores were significantly improved in these patients at the 24-month follow-up. The complication rate was 23% (3/13 patients). In non-responders, VAS and ODI at 24months dropped significantly as well but the decrease was less pronounced compared to responders and had not led to a decrease in pain medication. SPNS is a novel, safe, and effective treatment for CLBP and may have advantages over interventional treatments including intrathecal therapy and spinal cord stimulation.